2021
DOI: 10.1016/j.molcel.2021.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Timer-based proteomic profiling of the ubiquitin-proteasome system reveals a substrate receptor of the GID ubiquitin ligase

Abstract: Summary Selective protein degradation by the ubiquitin-proteasome system (UPS) is involved in all cellular processes. However, the substrates and specificity of most UPS components are not well understood. Here we systematically characterized the UPS in Saccharomyces cerevisiae . Using fluorescent timers, we determined how loss of individual UPS components affects yeast proteome turnover, detecting phenotypes for 76% of E2, E3, and deubiquitinating enzymes. We exploit this dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 139 publications
2
50
0
Order By: Relevance
“…In addition to Gid4, yeast cells express two alternative substrate receptors, Gid10 and Gid11, which all interact with the GID E3 ligase complex through Gid5/ARMC8 (Melnykov et al , 2019; Kong et al , 2021). Gid4 and Gid10 bind substrates containing nonproline degron motif (Dong et al , 2020), and further systematic screening identified many candidates that do not fulfill the Pro/N‐end degron criteria (Kong et al , 2021). Similarly, human GID4 may also recognize substrates such as ZMYND19 that lack Pro/N‐end degron motifs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to Gid4, yeast cells express two alternative substrate receptors, Gid10 and Gid11, which all interact with the GID E3 ligase complex through Gid5/ARMC8 (Melnykov et al , 2019; Kong et al , 2021). Gid4 and Gid10 bind substrates containing nonproline degron motif (Dong et al , 2020), and further systematic screening identified many candidates that do not fulfill the Pro/N‐end degron criteria (Kong et al , 2021). Similarly, human GID4 may also recognize substrates such as ZMYND19 that lack Pro/N‐end degron motifs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Cullin‐RING ligases (CRL) engage one out of a large family of substrate receptors, and their assembly is regulated by substrate availability and the exchange factor CAND1 (Pierce et al , 2013). In addition to Gid4, yeast cells express two alternative substrate receptors, Gid10 and Gid11, which all interact with the GID E3 ligase complex through Gid5/ARMC8 (Melnykov et al , 2019; Kong et al , 2021). Gid4 and Gid10 bind substrates containing nonproline degron motif (Dong et al , 2020), and further systematic screening identified many candidates that do not fulfill the Pro/N‐end degron criteria (Kong et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TFTs are fusions of a rapidly maturing green fluorescent protein (GFP) and a slower maturing red fluorescent protein (RFP) 58, 59 . The TFT’s ouput, expressed as the -log 2 RFP / GFP ratio, is directly proportional to its degradation rate and, when fused to N-degrons, measures UPS N-end rule activity 39, 55, 58 . Because the TFT is expressed as a single protein construct, the output of the TFT is also independent of its expression level 39, 55, 58, 60 , enabling its use in genetically diverse populations.…”
Section: Resultsmentioning
confidence: 99%
“…Most traits are genetically complex, shaped by many loci of small effect and few loci of large effect throughout the genome 36, 37 , suggesting that large-effect variants in UPS genes may represent only one extreme of a continuum of genetic effects on UPS activity. Moreover, variation in UPS activity can differentially affect the degradation of distinct UPS sub-strates 38, 39 . Whether genetic effects on UPS activity affect the turnover of distinct proteins consistently or in a substrate-specific manner remains a fundamentally open question.…”
Section: Introductionmentioning
confidence: 99%